Reduced graphene oxide (RGO) reinforced Mg biocomposites for use as orthopedic applications: Mechanical properties, cytocompatibility and antibacterial activity - Somayeh Abazari; Ali Shamsipur; Hamid Reza Bakhsheshi-Rad (Journal of Magnesium and Alloys, 2022)
Magnesium (Mg) has attracted wide interest in orthopedic applications as they exhibit great biodegradability and strong biocompatibility, while corrosion is the main concern for Mg that should be addressed prior to biomedical applications. In this work, ZM31 (Mg-3Zn-1Mn)/xRGO (x = 0, 0.5, 1 and 1.5 wt%) biocomposites were synthesized by semi-powder metallurgy method. The results showed that the RGO acting as an effective reinforcing filler to prevent deformation and showed better compressive strength (282.3 ± 9 MPa) and revealed enhancement in failure Strain (7.8 ± 2.1%) at 1 wt% RGO concentration compared to Mg alloy (244.5 ± 9 MPa and 7.1 ± 1.5% respectively). Moreover, fracture analysis indicated a more ductile fracture of the nanocomposites after the incorporation of RGO. Crack bridging, crack deflection and crack branching are dominant mechanisms for reinforcement of Mg-based containing RGO. Mg composites containing 0.5 wt% RGO showed a low corrosion rate (2.75 mm/year), while more incorporation of RGO resulted in an increased corrosion rate (4.38 mm/year). In addition, the degradation rate of ZM31 alloy (2.57 mg·cm−2·d−1) obviously decreased with the addition of 0.5 wt% RGO (1.84 mg·cm−2·d−1) in the SBF. Besides, continuous apatite layers were created on the composites in the SBF solution. Also, the cell culture examinations showed good cell viability and adhesion on composites with 0.5 and 1 wt% RGO, which was demonstrated by the SEM and MTT assay The alkaline phosphatase (ALP) activity of the ZM3–0.5RGO composite was considerably higher than that of ZM31 matrix alloy in 24 h and 48 h, implying higher osteoblastic differentiation. The antibacterial behavior toward both bacteria (E. coli and S. aureus) exhibited that escalating RGO concentration in Mg-matrix composites leads to further inhibition of bacteria growth. These findings suggested that ZM31–0.5RGO biocomposite could be a more promising candidate for orthopedic implants.